Biomedical Imaging Technologies: A Comparative Study of MRI, CT, and Ultrasound Innovations - Singh, Vikram (Journal of Advanced Research in Instrumentation and Control Engineering, 2025)
Biomedical imaging plays a crucial role in modern healthcare, offering non-invasive techniques for diagnosing, monitoring, and guiding treatments for various medical conditions. Advanced imaging technologies have significantly transformed clinical decision-making , enabling early disease detection and precise treatment planning. Among the most widely used imaging modalities, Magnetic Resonance Imaging (MRI), Computed Tomography (CT), and Ultrasound (US) stand out due to their diverse applications across multiple medical fields. MRI is known for its high soft-tissue contrast and radiation-free imaging , making it ideal for neurological, musculoskeletal, and oncological applications. CT provides rapid, high-resolution cross-sectional imaging , making it invaluable for emergency diagnostics, trauma assessment, and vascular imaging. Ultrasound, being portable, cost-effective, and real-time , is extensively used in obstetrics, cardiology, and point-of-care diagnostics. Recent innovations in biomedical imaging focus on enhancing resolution, speed, and accuracy while minimizing risks such as radiation exposure and scan-related artifacts. Advances such as AI-powered image reconstruction, photon-counting CT, elastography, and functional MRI (fMRI) are pushing the boundaries of imaging capabilities. Additionally, the integration of machine learning, deep learning algorithms, and hybrid imaging techniques (such as PET-MRI and CT-MRI) is revolutionizing image processing, analysis, and disease prediction. This review provides a comparative analysis of MRI, CT, and ultrasound, discussing their fundamental principles, clinical applications, benefits, and challenges. Furthermore, we explore the latest developments in contrast agents, AI-driven automation, and wearable imaging technologies , highlighting their potential to improve patient outcomes and advance precision medicine . The continuous evolution of biomedical imaging is shaping the future of healthcare, promising faster, safer, and more accurate diagnostic solutions for a wide range of medical conditions.